Lithic agency, Scottish modernism, and the politics of nuclear war. Issue 6 (2nd June 2020) - Gardiner, Michael; Stones, Andrew
ABSTRACT: This paper argues that entangledness with inorganic agency, particularly that of stone, not only speaks to recent object-oriented and ecocritical thought, but also marks a constitutional division within the UK, since 'thing power' implies a scepticism over the organic authority of an uncodified British constitution. The agency of stone undercuts the organicism of an eighteenth century understanding of natural law that can only understand the social as an 'evolving' association of individual property owners, demanding an ontological 'distance' from objects. Lithic agency was already of concern to 1920s-'30s Scottish modernists, notably Hugh MacDiarmid, but can be traced forward to anxieties over the 'totalising' or 'time-fixing' qualities of nuclear weapons. We describe this line of agential stone from modernism to the nuclear dramas of the 'New Cold War' era, and how it entails an ontological shattering of the British distance from objects. Depictions of the physical violence of nuclear standoff shatter the totalisation required by British natural law, pointing to a specifically Scottish and sub-British political aesthetic. An ontological division over nuclear weapons remains central to Scottish independence campaigns today – and their release of 'stony' and 'dusty' powers beyond the human provide a 'concrete' example for object-oriented thinking within literary theory after its geological turn.